Deafening noise down-regulates dopamine transmission in the hub of the central auditory system - Wilson, Patrick; Apawu, Aaron K. (Neurochemistry international, 2022)
The cumulative effects of noise are experienced across society regardless of occupation and age. Previous research has connected noise induced hearing disorders to neuronal changes within auditory brain regions, such as the inferior colliculus (IC), where the ascending and descending auditory neurons converge. Nevertheless, the neurochemical adaptations in the central auditory system underlining these disorders are not fully understood. Based on existing body of evidence that implicates dopamine (DA) in the central auditory processes, we hypothesized that alteration in the DA neurotransmission in the IC is a major neuroadaptation associated with noise-induced hearing loss. Using adult Sprague Dawley rat model in conjunction with an electrochemical method and immunoassay, this hypothesis was explored by characterizing the impact of noise on the DA system in the IC. Herein, slice fast scan cyclic voltammetry (FSCV) data revealed attenuation in stimulated DA release in the subjects exposed to deafening noise (10 kHz, 118 dB SPL, 1/3 octave band noise for 4 h) 24 h prior to the neurochemical measurements. DA receptor 2 (D2) functionality was also investigated as part of a possible negative feedback mechanism for the noise induced alteration, however no significant difference was observed between the noise exposed versus the control subjects. On the other hand, immunocytochemistry of the IC displayed marked difference in D2 receptor distributions overall and specifically, in the central and external nucleus of the IC. Taken together, these data link decrease DA neurotransmission in the IC to noise-induced hearing loss and show that while deafening noise does not directly impact the functionality of the D2 receptors, it does diminish the receptor density. Overall, these changes in the IC were demonstrated to be long-term and could be mediated by oxidative stress. •Noise-induced hearing related disorders are widespread and affect quality of life.•Effects of loud noise on dopamine neurotransmission in the inferior colliculus was examined.•Deafening noise attenuates dopamine release and D2 autoreceptor density.•Down-regulation in the dopamine transmission implicated in noise-induced deafness.